2017
DOI: 10.1152/ajpregu.00187.2017
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin does not acutely sensitize the reflex pressor response during hindlimb skeletal muscle stretch in decerebrate rats

Abstract: Hindlimb skeletal muscle stretch (i.e., selective activation of the muscle mechanoreflex) in decerebrate rats evokes reflex increases in blood pressure and sympathetic nerve activity. Bradykinin has been found to sensitize mechanogated channels through a bradykinin B2 receptor-dependent mechanism. Moreover, bradykinin B2 receptor expression on sensory neurons is increased following chronic femoral artery ligation in the rat (a model of simulated peripheral artery disease). We tested the hypothesis that injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…We used a dynamic stretch protocol in the present investigation because it replicates more closely the mechanical stimuli present when patients with PAD walk than does static hindlimb muscle stretch. Moreover, we have consistently found that chronic femoral artery ligation produces an exaggerated pressor response to dynamic stretch (present investigation, 8, 25), whereas there is not consensus on whether ligation exaggerates the pressor response to static hindlimb skeletal muscle stretch (26,27,33,48). Also consistent with the finding of Yamauchi et al (62), we found that EP4-R blockade reduced the pressor response to static hindlimb muscle contraction.…”
Section: Discussionsupporting
confidence: 87%
“…We used a dynamic stretch protocol in the present investigation because it replicates more closely the mechanical stimuli present when patients with PAD walk than does static hindlimb muscle stretch. Moreover, we have consistently found that chronic femoral artery ligation produces an exaggerated pressor response to dynamic stretch (present investigation, 8, 25), whereas there is not consensus on whether ligation exaggerates the pressor response to static hindlimb skeletal muscle stretch (26,27,33,48). Also consistent with the finding of Yamauchi et al (62), we found that EP4-R blockade reduced the pressor response to static hindlimb muscle contraction.…”
Section: Discussionsupporting
confidence: 87%
“…Pharmacological blockade of those receptors was found to reduce the pressor response during static stretch in ligated rats (29,57). Whether those findings have implications for our present investigation that utilized dynamic stretch is unclear, however, because femoral artery ligation has been found to augment the pressor response during static stretch in some studies (29,30,35,56, 57) but not in others (24,25,43,(52)(53)(54). In the present investigation, the pressor response during static stretch was not different between freely perfused and ligated hindlimbs.…”
Section: Chapter 4 -Discussionmentioning
confidence: 81%
“…However, whether findings from experiments in which static rat hindlimb muscle stretch is performed extend to experiments in which dynamic hindlimb muscle stretch is performed is unclear. That is an important point, especially considering that, compared with freely perfused rats, ligated rats do not consistently demonstrate an exaggerated pressor response during static hindlimb muscle stretch (26,46). Future investigations that examine the effect of EP4 and TxA 2 receptor blockade on the mechanoreflex evoked during dynamic hindlimb muscle stretch in ligated rats would be valuable.…”
Section: Soleusmentioning
confidence: 99%